A Case of a Two-Month-Old Boy Diagnosed with Infantile Crohn’s Disease Based on an Atypical Perianal Lesion - Kengo Nakaya; Yasushi Iinuma; Yutaka Hirayama; Yu Sugai; Shotaro Taki (Case Reports in Pediatrics)
Inflammatory bowel disease is rare in infants, and the early diagnosis is very important. We herein report an infant who received an early diagnosis of infantile Crohn’s disease (CD). A two-month-old boy presented with bloody stool. He developed a poor sucking tendency and a painful perianal lesion at three months of age. He was suspected of having infantile CD because of his atypical perianal lesion. Colonoscopy revealed that his perianal lesion had induced rectal longitudinal ulcers. Histology showed no granulomas but patchy inflammation reaching the submucosal layer. He was diagnosed with infantile CD based on the Japanese criteria. CD should be suspected in infants with atypical perianal lesions, irrespective of their age. Early colonoscopy with histology should be considered in these cases in order to prevent adverse outcomes in children.